2017
DOI: 10.1177/1075547016687998
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Climate Change Communication Through Online Games

Abstract: In search of innovative approaches capable of connecting climate change issues with teenagers, scholars and practitioners have become interested in harnessing the potential of gaming for advancing climate change communication. This article aims to propose a set of criteria, validated by experts through the Delphi method, by which to analyze communicative features of online climate change games. The use of the criteria is illustrated with an evaluation of a sample of Spanish games to which we apply qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…In summary, in order for games to be innovative and effective tools, as suggested by the gaming literature [Dudo et al, 2014;Fitts Willoughby and Smith, 2016;Meya and Eisenack, 2018;Ouariachi, Olvera-Lobo and Gutiérrez-Pérez, 2017], this study encourages a narrative turn in line with previous calls for the rethinking of climate change communication [e.g. Doyle, 2012;Doyle, 2015].…”
Section: Conceptual Thinking In Game Design and Everyday Experiences supporting
confidence: 77%
See 2 more Smart Citations
“…In summary, in order for games to be innovative and effective tools, as suggested by the gaming literature [Dudo et al, 2014;Fitts Willoughby and Smith, 2016;Meya and Eisenack, 2018;Ouariachi, Olvera-Lobo and Gutiérrez-Pérez, 2017], this study encourages a narrative turn in line with previous calls for the rethinking of climate change communication [e.g. Doyle, 2012;Doyle, 2015].…”
Section: Conceptual Thinking In Game Design and Everyday Experiences supporting
confidence: 77%
“…have confirmed that online games and gaming offer great potential as a novel and innovative communication strategy to inform the public and citizens about scientific research and engage them with it. In a study of online climate change games, Ouariachi, Olvera-Lobo and Gutiérrez-Pérez [2017] argue that games may offer an alternative to conventional media for delivering information. The relationships between game narrative and design and the communication of explicit meanings and implicit values, they argue, make games "innovative communication tools" [Ouariachi, Olvera-Lobo and Gutiérrez-Pérez, 2017, p. 36].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such tools also encouraged reflection about concrete local risks and adaptation actions (Glaas, Ballantyne, Neset, & Linnér, 2017). Similar studies have explored encouraging engagement with climate change through interactive graphics (Herring, VanDyke, Glenn Cummins, & Melton, 2016), through online games (Ouariachi, Olvera-Lobo, & Gutiérrez-Pérez, 2017;Reckien & Eisenack, 2013;Wu & Lee, 2015), and immersive virtual reality (Ahn et al, 2016;Joo, Ahn, Bailenson, & Park, 2014), and NGOs such as Greenpeace are making use of these technologies (Greenpeace, 2017). While there have been no assessments of Greenpeace's virtual reality app, other implementations of virtual reality devices have found them to be useful educational tools and a particularly powerful way to depict solutions (Moser & Daniels, 2017).…”
Section: Moving Pictures: Video and Visualizationsmentioning
confidence: 98%
“…Recently, there has been an increase in the development of online climate change gamesthat is, online video games specifically themed around climate change and/or related topics (Wu and Lee 2015). The technical sophistication, narrative, message framing, game dynamics, and pedagogical features of these communication and education tools vary (Ouariachi, Olvera-Lobo, and Guti errez-P erez 2017). They can be considered 'games for change', 'social impact games' or 'serious games', if they are intended to fulfil a purpose, convey ideas and values, and sometimes, to influence the players' thoughts and actions in real life (Frasca 2007).…”
Section: Introductionmentioning
confidence: 99%